Moscoso Sánchez, D., & Sánchez García, R. (Eds.) (2023). Sociología del Deporte. Dykinson. - Raúl A. Barba-Martín (Universidad Pablo de Olavide, 2024)
Recensión del libro Sociología del Deporte, de la Editorial Dykinson, editado en 2023.